The mystery horse - Warner, Gertrude Chandler, 1890-1979.; Tang, Charles (Morton Grove, Ill. : A. Whitman, 1993)
When their grandfather arranges for them to spend two week at Sunny Oaks, the four Alden children enjoy settling into the routines of farm life but become suspicious about a mysterious horse locked in the stables.
Keywords: Boxcar children (Fictitious characters) -- Juvenile fiction; Orphans -- Juvenile fiction; Families -- Juvenile fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Farm life -- Fiction; Horses -- Fiction; Mystery and detective stories; Detective and mystery stories